Effects of Jump Difficulty on the Final Performance in Snowboard-Slopestyle-Winter Olympic Games, Socchi 2014 - Jesús Muñoz; Javier García-Rubio; David Ramos; Kiko León; Daniel Collado-Mateo (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Despite the increasing popularity of the snowboard, there is not scientific literature for sport performance indicators in this sport. Objectives. To analyze the effects of jump difficulty on the final performance during snowboarding-slopestyle competition. Methods. All competition sequences (n=214) from the 2014 Winter Olympic Games were analyzed. Of these, 123 were from the men´s competition and 91 were from the women´s competition. The interaction between the final score and number of rotations was calculated using regression models with quadratic or linear equations. All analyses were performed separately for women and men. Results. Quadratic regression had better R2 and mean absolute errors than linear regression. Linear and quadratic regressions showed that the number of rotations significantly predicts final score in men.  However, in the women´s competition, the curve of quadratic regression was almost identical to that from the linear regression. Conclusion. These results have identified the importance of evaluating the jump difficulty versus its efficacy. Athletes and coaches have to weigh pros and cons of increasing the difficulty of jumps or improve jumps that are already fluent in order to master them.